LEARNING WITH THE TA'LIM AL-MUTA'ALLIM BOOK IN FORMING THE MORALS OF STUDENTS AT THE AL-MUTTAQIN ISLAMIC BOARDING SCHOOL IN SITUMANG, WEST PASAMAN - Rahman, Abdul; Fitria, Mita; Rahmadi; Rahmat (Amanah Publishing, 2024)
This research is motivated by the phenomenon of declining morals among some students at the Al-Muttaqin Islamic Boarding School in Situmang, West Pasaman. Although the Ta'lim Al-Muta'allim textbook has been implemented as a guideline for their pursuit of knowledge, behaviors that do not reflect good moral values ​​are still found, such as a lack of respect for teachers, knowledge, and peers. This condition raises the need to evaluate how the implementation of this textbook can strengthen the moral formation of students so that it aligns with the goals of Islamic boarding school education. The purpose of this study is 1) To find out the planning of learning the Ta'lim Al-Muta'allim book on the chapter of glorifying knowledge and teachers in the formation of students' morals at the Al-Muttaqin Islamic Boarding School, Situmang, West Pasaman, 2) To find out the implementation of learning the Ta'lim Al-Muta'allim book on the chapter of glorifying knowledge and teachers in the formation of students' morals at the Al-Muttaqin Islamic Boarding School, Situmang, West Pasaman, 3) To find out the implications of implementing the learning of the Ta'lim Al-Muta'allim book on the chapter of glorifying knowledge and teachers in the formation of students' morals at the Al-Muttaqin Islamic Boarding School, Situmang, West Pasaman. This type of research is descriptive qualitative research. Data were collected through interviews with Murobbi, student supervisors, and students, as well as observation and documentation. This approach aims to describe in depth the implementation of learning the Ta'lim Al-Muta'allim book in the formation of students' morals at the Al-Muttaqin Islamic Boarding School, Situmang, West Pasaman. The results of the study indicate that: 1) The learning planning of the Ta'lim Al-Muta'allim book at the Al-Muttaqin Islamic Boarding School has been well-structured, including the determination of clear learning objectives, interactive lecture and discussion methods, and the existence of written rules that serve as guidelines for murobbi and musrif, 2) The implementation of learning runs effectively with the support of collaboration between murobbi and student mentors. Students are encouraged to understand the material theoretically and practice it in everyday life. However, some students still have difficulty connecting theory with practice, especially in internalizing the value of honoring knowledge and teachers, 3) The implications of learning implementation are seen from the improvement of students' morals, such as the growth of discipline, humility, and respect for teachers and peers. In addition, there are positive behavioral changes such as increased learning motivation and student responsibility in Islamic boarding school activities.